2020
DOI: 10.3390/app10238438
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Soybean Oil Supplemented with Ginger and Turmeric Powders

Abstract: Soybean oil has been supplemented with 10% (w/w) of ginger and turmeric powders derived from commercial products (GC—commercial ginger and TC—commercial turmeric), freeze-dried rhizomes (freeze-dried ginger (GR) and freeze-dried turmeric rhizome—TR) and peels (freeze-dried ginger peel (GP) and freeze-dried turmeric peel—TP) for developing a functional seasoning with great lipid stability for human consumption. The exhausted ginger and turmeric powders were also recovered and recycled two times to promote a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…For this reason, oxidative stability is one of the most important parameters assessed in the formulation of commercial oils (Tinello et al, 2018) since the undesirable compounds formed would impair the properties of not only the oil but also the fried food. In the free radical chain reaction of lipid oxidation, described by the stages of initiation, propagation, and termination, oxygen plays an important role, so the addition of antioxidants, as free radical scavengers before the propagation phase, is considered a strategy to control the lipid autoxidation and to enhance the lag time until the production of the volatile compounds, which are markers of rancidity (Tinello et al, 2020). For this reason, the food industry faces antioxidants as necessary additives (Choe & Min, 2009), such as the synthetic one butylated hydroxytoluene (BHT).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, oxidative stability is one of the most important parameters assessed in the formulation of commercial oils (Tinello et al, 2018) since the undesirable compounds formed would impair the properties of not only the oil but also the fried food. In the free radical chain reaction of lipid oxidation, described by the stages of initiation, propagation, and termination, oxygen plays an important role, so the addition of antioxidants, as free radical scavengers before the propagation phase, is considered a strategy to control the lipid autoxidation and to enhance the lag time until the production of the volatile compounds, which are markers of rancidity (Tinello et al, 2020). For this reason, the food industry faces antioxidants as necessary additives (Choe & Min, 2009), such as the synthetic one butylated hydroxytoluene (BHT).…”
Section: Introductionmentioning
confidence: 99%
“…Tinello and others،2020 [19] Components in the Fumaria parvifora L. extract were found to be able to scavenge free radicals via electron and hydrogen donating processes, and to block or slow the onset of free radical mediated chain reaction, according to the results of the DPPH free radical scavenging assay.…”
Section: Ginger and Turmeric Powdersmentioning
confidence: 98%
“…The sunflower oil was extracted using a Soxhlet device, and the n-hexane solvent was used to extract the oil at a temperature of 80 °C, the extraction continued for 8-12 hours. Then the sunflower oil and IOP Publishing doi:10.1088/1755-1315/1262/6/062038 3 the solvent were added In a rotary evaporator at 6°C for half an hour until the hexane solvent was removed, after that it was placed at a temperature of 70°C to get rid of the remaining hexane [12].…”
Section: Extractionmentioning
confidence: 99%
“…Also, the researcher Abd-ElGhany and others, (2010) [23]. indicated when studying olive extract as a natural antioxidant to improve the stability of sunflower oil, and the results showed a decrease in viscosity between (67.52, 65.80, 61.88, 60.57) centigrade during periods (0, 4,8,12). day at a temperature of 35 C. They concluded that the reason for the decrease in viscosity is due to the storage temperature, which led to the oxidation of the double bonds of the fatty acids.…”
Section: Viscositymentioning
confidence: 99%